Mechanisms of U46619‐induced contraction in mouse intrarenal artery. (17th April 2019) - Yan, Hong; Zhang, Meng‐Zhen; Wong, Gordon; Liu, Lin; Kwok, Yat Sze (Shelia); Kuang, Su‐Juan; Yang, Hui; Rao, Fang; Li, Xin; Mai, Li‐Ping; Lin, Qiu‐Xiong; Yang, Min; et al.
Summary: Thromboxane A2 (TXA2 ) has been implicated in the pathogenesis of vascular complications, but the underlying mechanism remains unclear. The contraction of renal arterial rings in mice was measured by a Multi Myograph System. The intracellular calcium concentration ([Ca 2+ ]i ) in vascular smooth muscle cells (VSMCs) was obtained by using a fluo‐4/AM dye and a confocal laser scanning microscopy. The results show that the U46619‐induced vasoconstriction of renal artery was completely blocked by a TXA2 receptor antagonist GR32191, significantly inhibited by a selective phospholipase C (PI‐PLC) inhibitor U73122 at 10 μmol/L and partially inhibited by a Phosphatidylcholine ‐ specific phospholipase C (PC‐PLC) inhibitor D609 at 50 μmol/L. Moreover, the U46619‐induced vasoconstriction was inhibited by a general protein kinase C (PKC) inhibitor chelerythrine at 10 μmol/L, and a selective PKCδ inhibitor rottlerin at 10 μmol/L. In addition, the PKC‐induced vasoconstriction was partially inhibited by a Rho‐kinase inhibitor Y‐27632 at 10 μmol/L and was further completely inhibited together with a putative IP3 receptor antagonist and store‐operated Ca 2+ (SOC) entry inhibitor 2‐APB at 100 μmol/L. On the other hand, U46619‐induced vasoconstriction was partially inhibited by L‐type calcium channel (Cav1.2) inhibitor nifedipine at 1 μmol/L and 2‐APB at 50 and 100 μmol/L. Last, U46619‐induced vasoconstriction was partially inhibited by a cell membrane Ca 2+ activated C1 − channel blocker 5‐Nitro‐2‐(3‐phenylpropylamino) benzoic acid (NPPB) at 50 and 100 μmol/L. Our results suggest that the U46619‐induced contraction of mouse intrarenal arteries is mediated by Cav1.2 and SOC channel, through the activation of thromboxane‐prostanoid receptors and its downstream signaling pathway.